Determining Hair Thickness using the Light Diffraction Method: Verification of the Seven Times Sliced Hair Phenomenon - Ellianawati Ellianawati; Muhammad An’im Arravi; Fitria Wulandari; Rofita Istiqomah (Journal of Natural Sciences and Mathematics Research, 2018)
Light or optical spectrum is a part of electromagnetic radiation and has several electromagnetic wave properties; one of them is undergoing diffraction. Diffraction or light bending occurred when a light went through a narrow gap. By utilizing that principle, it was proven that a piece of hair could be assumed as a single gap, so the thickness of a piece of hair could be determined, which lead to the explanation of the phenomenon of a piece of hair sliced seven times.  As a tool, the used sim cardholder is used to put hair using adhesive tape. Then the sim card is placed between the light source and the screen. The light source used is a red laser with a wavelength of 660 nm. Hair is placed in two positions: horizontally and vertically. Hair that is laid horizontally will create a vertical light-dark pattern, and hair that is placed vertically will form a horizontal light-dark pattern. The dark and light patterns on the screen are measured using a ruler according to the order of each pattern that is formed. The hair thickness measurement results using a red laser with a wavelength of 660 nm obtained hair thickness of d = (0.01146 ± 0.00019) cm for hair that is placed horizontally and d = (0.01151 ± 0.00011) cm for vertically placed hair. This data has more or less proven that there is potential to "split" the hair into sections, but it has not been proven that the hair can be split into seven parts, so there is still a chance to prove it.